2022
DOI: 10.1021/acs.jafc.2c03459
|View full text |Cite
|
Sign up to set email alerts
|

Lysostaphin: Engineering and Potentiation toward Better Applications

Abstract: Lysostaphin is a potent bacteriolytic enzyme with endopeptidase activity against the common pathogen Staphylococcus aureus. By digesting the pentaglycine crossbridge in the cell wall peptidoglycan of S. aureus including the methicillin-resistant strains, lysostaphin initiates rapid lysis of planktonic and sessile cells (biofilms) and has great potential for use in agriculture, food industries, and pharmaceutical industries. In the past few decades, there have been tremendous efforts in potentiating lysostaphin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 212 publications
0
3
0
Order By: Relevance
“…Additionally, compared with TEV protease that is confronted with low yield, poor solubility, and instability during recombinant expression, lysostaphin can be expressed with high yields and stability intracellularly or extracellularly in various hosts including E. coli, Bacillus subtilis, Lactococcus lactis, Pichia pastoris, and mammalian cells as long as the codons are optimized according to the preference of the hosts and the glycosylation sites are mutated (for eukaryotic systems). ,,, This feature greatly facilitates lysostaphin production at both the lab scale and the industrial scale. However, it is worth noting that lysostaphin as a protease has its intrinsic limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, compared with TEV protease that is confronted with low yield, poor solubility, and instability during recombinant expression, lysostaphin can be expressed with high yields and stability intracellularly or extracellularly in various hosts including E. coli, Bacillus subtilis, Lactococcus lactis, Pichia pastoris, and mammalian cells as long as the codons are optimized according to the preference of the hosts and the glycosylation sites are mutated (for eukaryotic systems). ,,, This feature greatly facilitates lysostaphin production at both the lab scale and the industrial scale. However, it is worth noting that lysostaphin as a protease has its intrinsic limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Lysostaphin is an endopeptidase naturally secreted by Staphylococcus simulans biovar staphylolyticus against the competing bacterium Staphylococcus aureus (S. aureus), and it cleaves the cell wall peptidoglycan of S. aureus via specific digestion of the pentaglycine crossbridge. 6 Besides the natural cell wall of S. aureus, lysostaphin is also able to digest synthetic peptides such as N-acetylhexaglycine, 7 oligoglycine containing two to six glycine residues, 8 and KGGGGG/AEKAGGGGG peptides with different fluorescent tags. 9,10 Surprisingly, in a study of identifying elastin-binding proteins in S. aureus using an elastin column, it was found that lysostaphin used to solubilize the cells was bound to the column and could digest elastin, which is an insoluble protein with one-third of its amino acids being glycine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation